PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP LOYALITAS NASABAH PADA KANTOR PT. PEGADAIAN CABANG UPC BARAKA, KABUPATEN ENREKANG - Anugrah, Anugrah; Romadoni, Buyung; Ihsan Burhanuddin, Chairul (LPPM - STIE SAKTI ALAM KERINCI, 2026)
This study aims to determine the effect of service quality and promotion on customer loyalty at PT. Pegadaian UPC Baraka. The background of this research is driven by fluctuations in the number of customers and the effectiveness of marketing strategies. The method used is quantitative associative with a population of 2,400 active customers in 2024. The sampling technique utilized the Slovin formula with a 10% margin of error, resulting in 96 respondents. Primary data were collected through questionnaires, while secondary data were obtained through the company's internal reports. Data analysis was performed using parametric statistical tests, including partial (t) and simultaneous (F) tests. The results showed that partially, service quality has a positive but insignificant effect on customer loyalty (t count 0.935 < t_table 1.661; sig 0.352). This is because customers prioritize the speed of fund disbursement over service aspects. Meanwhile, the promotion variable has a positive and significant effect on loyalty (t count 3.899 > t_table 1.661; sig 0.000), making it the most dominant factor. Simultaneously, service quality and promotion have a significant influence on customer loyalty (F count 99.625 > F table 3.10; sig 0.000) with a coefficient of determination (Adjusted R²) of 0.675. This finding confirms that 67.5% of customer loyalty is determined by the combination of service and promotion. Management is advised to continue optimizing digital and conventional promotional strategies without neglecting service quality standards to create stronger and sustainable emotional engagement with customers in the future. Keywords: Service Quality, Promotion, Customer Loyalty, Pegadaian.",